Data for: Changes in Secondary Organic Aerosol Composition and Volatility Going from a Low to a High HO2/RO2 Regime in α-Pinene Photooxidation - Geretti, Veronica; Hallquist, Mattias (University of Gothenburg, 2026)
Here are reported data from chamber experiments of Secondary Organic Aerosol (SOA) formation from α-pinene under more atmospherically relevant hydroperoxyl radicals (HO2) to peroxy radicals (RO2) ratio. Our result shows reduced SOA formation and increased volatility from low to high HO2/RO2 conditions.

The experiments were run in steady-state conditions in the SAPHIR STAR stirred tank reactor. The particle-phase was characterized with a Filter Inlet for Gases and AEROsols coupled with an iodide Chemical Ionization Mass Spectrometer (FIGAERO-CIMS), and a CIMS with NO3- ionization was used for gas-phase measurements.

The particle-phase data is normalized by reagent ion (iodide) and water.
The blank filter from empty chamber was subtracted (see supplements for more info).
The particle-phase data is in counts/m3 resulting from integration of the individual thermograms and normalization by sampled volume and sampling time. The 2 repeated desorption thermograms were averaged to one.
The GUFIT (explained in the manuscript and supplemental material) was applied to the thermograms. The reported data consists of the EMG1 area of the thermograms.
The Tmax values extracted are reported together with the calculated logC* values.
The LogC* were calculated utilizing a combined approach based on Tmax and logC* parameterization from Peräkylä et al. (2020), see manuscript for more details.
The gas-phase consists of averaged counts per second and the standard deviation of the steady state sampling.
The gas-phase data is normalized by the TIC of the NO3CIMS, and chamber and instrumental background is subtracted.

The data sheets consist of one value for compound. The compounds are reported with their chemical formula and their summed mass. Both gas and particle phase data are normalized by alpha-pinene turnover (see manuscript for details).

Rapporterade data från kammarförsök av sekundär organisk aerosol (SOA)-bildning från α-pinen under atmosfäriskt relevanta förhållanden med förhållandet mellan hydroperoxylradikaler (HO₂) och peroxiradikaler (RO₂). Våra resultat visar minskad SOA-bildning och ökad flyktighet från låga till höga HO₂/RO₂-förhållanden. Se den engelska sidan för en mer fullständig beskrivning
Data för: Changes in Secondary Organic Aerosol Composition and Volatility Going from a Low to a High HO2/RO2 Regime in α-Pinene Photooxidation
Keywords: secondary organic aerosol; secondary organic aerosol; volatility; volatility; peroxy radicals; peroxy radicals; chemical composition; chemical composition; alpha pinene; alpha pinene; hydroperoxyl radicals; hydroperoxyl radicals; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap